Treatment outcomes and risk factors of death in childhood tuberculous meningitis in Kandahar, Afghanistan: a prospective observational cohort study - Rahimi, BA; Niazi, N; Rahimi, AF; Faizee, MI; Khan, MS; Taylor, WR (Oxford University Press, 2022)
Background: Tuberculous meningitis (TBM) is the most severe form of TB. We prospectively documented the treatment outcomes and the risk factors for death in children with TBM from Kandahar, Afghanistan. Methods: This prospective observational cohort study was conducted from February 2017 to January 2020 in hospitalised TBM children. All the patients were prospectively followed up for 12 mo. Data were analysed by using descriptive statistics, χ2 and multivariate logistic regression. Results: A total of 818 TBM hospitalised patients with median age 4.8 (0.8–14.5) y were recruited. Females accounted for 60.9% (498/818). Upon admission 53.9% (n=441) and 15.2% (n=124) had TBM stages II and III, respectively, and 23.2% (n=190) had focal neurological signs. The case fatality rate was 20.2% (160/794) and 30.6% (243/794) survived with neurological sequelae. Independent risk factors for death were being unvaccinated for BCG (adjusted OR [AOR] 3.8, 95% CI 1.8 to 8.1), not receiving dexamethasone (AOR 2.5, 95% CI 1.5 to 4.2), being male (AOR 2.3, 95% CI 1.5 to 3.6), history of recent weight loss (AOR 2.2, 95% CI 1.3 to 3.9) and having stage III TBM (AOR 2.0, 95% CI 1.2 to 3.3). Conclusions: TBM continues to cause high morbidity and mortality in Afghan children. Strategies to reduce mortality should emphasise early diagnosis and treatment, routine use of dexamethasone and increased BCG vaccination.